2015
DOI: 10.1021/acsnano.5b04974
|View full text |Cite
|
Sign up to set email alerts
|

Exciton–Plasmon Coupling Enhancement via Metal Oxidation

Abstract: In this paper, we report on the effect of metal oxidation on strong coupling interactions between silver nanostructures and a J-aggregated cyanine dye. We show that metal oxidation can sensibly affect the plexcitonic system, inducing a change in the coupling strength.In particular, we demonstrate that the presence of oxide prevents the appearance of Rabi splitting in the extinction spectra for thick spacers. In contrast, below a threshold percentage, the oxide layer results in an higher coupling strength betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 68 publications
4
36
0
Order By: Relevance
“…analogously to Eqs. (21) and (35). One can also introduce the far-field amplitude F rad of the total field by replacing E sca , F, P, and W sca in Eqs.…”
Section: Energy Budget For Sources Near a Scatterermentioning
confidence: 99%
See 2 more Smart Citations
“…analogously to Eqs. (21) and (35). One can also introduce the far-field amplitude F rad of the total field by replacing E sca , F, P, and W sca in Eqs.…”
Section: Energy Budget For Sources Near a Scatterermentioning
confidence: 99%
“…Unfortunately, W enh cannot be directly simplified analogously to Eqs. (21) and (35) due to the lack of symmetry between the two vector functions on the left and right sides ofḠ. However, combining it with W ext [Eq.…”
Section: Energy Budget For Sources Near a Scatterermentioning
confidence: 99%
See 1 more Smart Citation
“…From the experimental side, in recent years, PEPs have been reported in emitter ensembles [10][11][12][13], in which excitonic nonlinearities are negligible [14][15][16]. Only very recently, thanks to advances in the fabrication and characterization of large Purcell enhancement nanocavities [17][18][19], far-field signatures of plasmonexciton strong coupling for single molecules have been reported experimentally [20].…”
mentioning
confidence: 99%
“…Recent studies have shown that strong coupling can be introduced to modify molecular system physicochemical characteristics . Strong coupling between the ground and excited states can modulate photochemical properties, work functions, and phase transitions. Cavity–vibration strong coupling can regulate specific chemical bond vibrational frequencies within a molecule .…”
Section: Strong Coupling Practical Applicationsmentioning
confidence: 99%